NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL IBUK KARYA IWAN SETYAWAN - Cintya Nurika Irma (Universitas Negeri Makassar, 2018)
Abstract: Values of Character Education in Novel Ibuk Karya Iwan Setiawan. This study aims to describe the values of character education contained in Novel Ibuk by Iwan Setyawan. Research is designed with qualitative approach. Data were collected by using the method of reading and record and analyzed descriptive qualitative. The results showed that there were 12 values of character education in Ibuk novels, including (1) simple living, (2) responsibility, (3) affection, (4) filial piety, (5) religious, (6) caring, (7) appreciating achievement, (8) hard work, (9) love homeland, (10) honest, (11) empathy, and (12) like to read. Based on these findings, Novel Ibuk deserves to be used as teaching materials for literature in high school because it contains many educational values.